Achieving the tradeoffs between pollutant discharge and economic benefit of the Henan section of the South-to-North Water Diversion Project through water resources-environment system management under uncertainty. (25th October 2021) - Li, Donglin; Zuo, Qiting; Wu, Qingsong; Li, Qianwen; Ma, Junxia
Abstract: Environmental water quality problems resulting from pollutant discharges have received extensive attention with the increasingly severe challenges facing global resources and the environment. A consideration of hierarchy within water resources-environment system (WRES) management under uncertainty can effectively improve the accuracy and applicability of management decisions. This study developed an interval fuzzy-credibility constrained two-level programming (IFCTP) model for WRES planning which considers uncertain information through the use of interval values and fuzzy sets and can also resolve conflicting goals among decision-makers in different departments. The IFCTP-WRES model was then formulated and applied for planning of the middle route of South-to-North Water Diversion Project (SNWDP) in Henan Province, China. Multiple water allocation, pollution control, and economic benefit solutions encompassing three departments and thirteen water-receiving cities involving dual uncertainties and varied credibility levels were examined. The results showed that: (1) the proportion of water resources allocated to ecological flows should increase from [14.12, 14.15]% to [17.97, 17.99]% over the entire planning period; (2) the proportion of water resources allocated to small cities (e.g., Huaxian County) should show a constant increase; (3) municipal wastewater can contribute more than half of the total pollutant load; (4) as compared to the economic benefit that can be obtained through solutions identified by two single-objective models, the interval fuzzy-credibility constrained programming environmental management system (IFCP-EMS) model and interval fuzzy-credibility constrained programming water resources management system (IFCP-WMS) model, that by the IFCTP-WRES model has higher by 5.0% and lower by 4.5%, respectively. These findings can provide abundant alternatives for achieving sustainable development and can help decision-makers to effectively plan WRES management under uncertainty. Graphical abstract: Image 1 Highlights: An interval fuzzy-credibility constrained two-level programing approach was developed. An IFCTP-WRES model was applied to plan the SNWDP in Henan province. Achieving tradeoffs of pollutant discharge and economic benefit through this model. Pollutants from domestic water are the major contributor of environmental pollution. Findings can provide direct support for the synthesized management of WRES.